Predictive Factors for Positive Surgical Margins in Patients With Prostate Cancer After Radical Prostatectomy: A Systematic Review and Meta-Analysis - Zhang, Lijin; Zhao, Hu; Wu, Bin; Zha, Zhenlei; Yuan, Jun; Feng, Yejun (Frontiers in Oncology, 2021)
Background and objectives: Previous studies have demonstrated that positive surgical margins (PSMs) were independent predictive factors for biochemical and oncologic outcomes in patients with prostate cancer (PCa). This study aimed to conduct a meta-analysis to identify the predictive factors for PSMs after radical prostatectomy (RP). Methods: We selected eligible studies via the electronic databases, such as PubMed, Web of Science, and EMBASE, from inception to December 2020. The risk factors for PSMs following RP were identified. The pooled estimates of standardized mean differences (SMDs)/ odds ratios (ORs) and 95% confidence intervals (CIs) were calculated. A fixed effect or random effect was used to pool the estimates. Subgroup analyses were performed to explore the reasons for heterogeneity. Results: Twenty-seven studies including 50,014 patients with PCa were eligible for further analysis. The results showed that PSMs were significantly associated with preoperative prostate-specific antigen (PSA) (pooled SMD=0.37; 95% CI:0.31–0.43; P<0.001), biopsy Gleason Score (< 6/ ≥7) (pooled OR=1.53; 95% CI:1.31–1.79; P<0.001), pathological Gleason Score (< 6/ ≥7) (pooled OR= 2.49; 95% CI:2.19–2.83; P<0.001), pathological stage (